Optimization of IMC on Ponpes Mazilah in Pesantren-Based Economic Empowerment with the Utilization of CMS Website - Agustina, Della; Nurbaiti, Nurbaiti; Aslami, Nuri; Ihwan, Ali; Nurafni, Anggi (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2024)
Pondok pesantren have an important role in economic empowerment to create independence for the pesantren itself. The situation of pesantren life in the past is certainly different from today, pesantren need to take modern steps to create their independence. Integrated Marketing Communication (IMC) is a modern marketing communication concept that can support the economic empowerment of pesantren with measurable and comprehensive steps. In the midst of competition to get the attention and positive response of the community, every pesantren needs to optimize IMC by utilizing the Content Management System (CMS) as a medium of information and promotion. Departing from the urgency of optimizing IMC by utilizing the CMS website, the problem actually exists in Pesantren Mazilah Darussalam Deli Serdang as a community service partner. As a pesantren that stands in this modern era, Mazilah Darussalam has not optimized IMC by utilizing the CMS website-based information and promotion media space, even though this is important to do to open wide access to the community. The purpose of this service is to support the pesantren to provide access to information for the public as a basic step of empowerment for pesantren. The method used is by conducting socialization and education related to marketing communication through website management. The result of this service is to provide recommendations for website page forms as a reference for Mazilah Darussalam to utilize CMS.